Fermi Large Area Telescope Observations of the Vela Pulsar - Abdo, A.; Ackermann, M.; Atwood, W.; Bagagli, R.; Baldini, L.; Ballet, J.; Band, D.; Barbiellini, G.; Baring, M.; Bartelt, J.; Bastieri, D.; Baughman, B.; et al. (Institute of Physics Publishing, 2009)
The Vela pulsar is the brightest persistent source in the GeV sky and thus is the traditional first target for new gamma-ray observatories. We report here on initial Fermi Large Area Telescope observations during verification phase pointed exposure and early sky survey scanning. We have used the Vela signal to verify Fermi timing and angular resolution. The high-quality pulse profile, with some 32,400 pulsed photons at E >= 0.03 GeV, shows new features, including pulse structure as fine as 0.3 ms and a distinct third peak, which shifts in phase with energy. We examine the high-energy behavior of the pulsed emission; initial spectra suggest a phase-averaged power-law index of Gamma = 1.51+0.05 -0.04 with an exponential cutoff at Ec = 2.9 ± 0.1 GeV. Spectral fits with generalized cutoffs of the form e^{-(E/E_c)^b} require b <= 1, which is inconsistent with magnetic pair attenuation, and thus favor outer-magnetosphere emission models. Finally, we report on upper limits to any unpulsed component, as might be associated with a surrounding pulsar wind nebula.